TECHNOLOGY OF HEATING OF THE UNINTERRUPTEDLY CASTED SLUGS IN THE FURNACE OF MILL 150 RUP “BELORUSSIAN METALLURGICAL WORKS” AT THE MINIMUM POSSIBLE FUEL CONSUM PTION - V. I. Timoshpolskij; D. N. Andrianov; S. M. Kabishov; V. A. Tishchenko; V. A. Shcherbakov (Литьë и металлургия)
There are carried out the complex investigations of thermal work of the heating furnace of the mill 250 RUP ''Belorussian metallurgical works” using the methods of nonlinear mathematical modeling and the theory of optimal control.